The Pharmacist and Quality of Patient Care - Kishore, Githa (Indian Journal of Pharmacy Practice)
Pharmaceutical care essentially is the acceptance of a social responsibility for the healthcare needs of an individual patient by a pharmacist. It is patient-centric and outcomes oriented. Its primary objectives are to promote health, to prevent disease and to assess, monitor, initiate and modify medication use to ensure that drug therapy regimens are safe and effective for the patient. It is the responsible provision of drug therapy for the purpose of achieving definite health related outcomes that improve a patient’s quality of life. As medical advances have led to cures and improved treatments of disease and delayed mortality, it is logical for a pharmacist to be involved in not only saving lives but also in terms of improving the quality of patients’ lives.